Candida albicans Yeast, Pseudohyphal, and Hyphal Morphogenesis Differentially Affects Immune Recognition - Mukaremera, Liliane; Lee, Keunsook K.; Mora-Montes, Hector M.; Gow, Neil A. R. (Frontiers in Immunology, 2017)
Candida albicans is a human opportunist pathogen that can grow as yeast, pseudohyphae or true hyphae in vitro and in vivo, depending on environmental conditions. Reversible cellular morphogenesis is an important virulence factor that facilitates invasion of host tissues, escape from phagocytes and dissemination in the blood stream. The innate immune system is the first line of defence against C. albicans infections and is influenced by recognition of wall components which vary in composition in different morphological forms. However, the relationship between cellular morphogenesis and immune recognition of this fungus is not fully understood. We therefore studied various vegetative cell types of C. albicans, singly and in combination, to assess the consequences of cellular morphogenesis on selected immune cytokine outputs from human monocytes. Hyphae stimulated proportionally lower levels of certain cytokines from monocytes per unit of cell surface area than yeast cells, but did not suppress cytokine response when co-presented with yeast cells. Pseudohyphal cells induced intermediate cytokine responses. Yeast monomorphic mutants had elevated cytokine responses under conditions that otherwise supported filamentous growth and mutants of yeast and hyphal cells that were defective in cell wall mannosylation or lacking certain hypha-specific cell wall proteins could variably unmask or deplete the surface of immunostimulatory ligands. These observations underline the critical importance of C. albicans morphology and morphology-associated changes in the cell wall composition that affect both immune recognition and pathogenesis.